2018
DOI: 10.1002/adsc.201800989
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Dehydrogenative Cross‐Coupling of Quinoxalin‐2(1H)‐ones with Amines for the Synthesis of 3‐Aminoquinoxalinones

Abstract: An efficient protocol for the synthesis of 3-aminoquinoxalinones via the electrochemical dehydrogenative C-3 amination of quinoxalin-2(1H)-ones was developed. With aliphatic amines and azoles as the nitrogen sources, a series of 3-aminoquinoxalinones was obtained in up to 99% yield. This direct electrolytic method avoids the use of transition metals and external oxidants, and represents an appealing alternative for the synthesis of 3-aminoquinoxalinones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(34 citation statements)
references
References 44 publications
1
33
0
Order By: Relevance
“…Meanwhile, substrate 2 a presented no obvious oxidation peak ranging from −1.0 to 3.0 V versus Ag/AgCl. Furthermore, the CV of mixture of 1 a with 2 a demonstrated oxidant peaks at 1.3 V and 2.1 V. These results indicated that this electrochemical oxidative coupling might begin with the oxidation of 1 a at anode, which is different from Zeng's proposed mechanism in their oxidative amination work …”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…Meanwhile, substrate 2 a presented no obvious oxidation peak ranging from −1.0 to 3.0 V versus Ag/AgCl. Furthermore, the CV of mixture of 1 a with 2 a demonstrated oxidant peaks at 1.3 V and 2.1 V. These results indicated that this electrochemical oxidative coupling might begin with the oxidation of 1 a at anode, which is different from Zeng's proposed mechanism in their oxidative amination work …”
Section: Resultsmentioning
confidence: 64%
“…Compounds containing quinoxalinone moiety are frequently employed as building blocks in pharmaceutical industry. Significant achievements have been recently realized for the direct C3−H functionalization of quinoxalin‐2(1 H )‐ones, including amidation, amination, acylation, arylation, fluoroalkoxylation . Also, Cui et al .…”
Section: Introductionmentioning
confidence: 99%
“…Next, the loading of catalyst was evaluated and the result revealed that 10% of Cu(PF 6 ) • 4CH 3 CN was suitable for the reaction with the yield of 3 a increasing to 78% (Table 1, entries [12][13]. Subsequently, diverse oxidants including Na 2 S 2 O 8 , PhI(OAc) 2 and PIFA ([Bis (trifluoroacetoxy)iodo]benzene) were also tested again and the results showed that (NH 4 ) 2 S 2 O 8 still was the most appropriate oxidant among the aforementioned oxidants (Table 1, entries [14][15][16]. Finally, several bases (Cs 2 CO 3 , KOAc, etc.)…”
Section: Resultsmentioning
confidence: 99%
“…In the case of N-substituents, either unsubstituted, N-alkylor N-allyl-substituted derivatives reacted equally well to give the corresponding products in excellent yields. Zeng and co-workers 52 have demonstrated an electrochemical method for the direct C3 amination of quinoxalin-2(1H)-one derivatives. Many secondary amines reacted well under the optimized conditions to afford the desired 3-aminoquinoxalin-2(1H)-one derivatives (Scheme 59).…”
Section: Syn Thesismentioning
confidence: 99%